2021
DOI: 10.1080/01616412.2021.1980842
|View full text |Cite
|
Sign up to set email alerts
|

C-Reaction Protein and the Severity of Intracerebral Hemorrhage: A Study from Chinese Stroke Center Alliance

Abstract: Background: Intracerebral hemorrhage (ICH) has a high mortality and morbidity in the world. C-Reaction Protein (CRP) has been demonstrated to be an independent risk factor and could predict the severity and outcome of ischemic stroke. In our study, we aimed to find out the relationship between CRP levels and the severity and outcome of patients with ICH. Methods: This study comes from the Chinese Stroke Center Alliance (CSCA). Patients' basic characteristics and laboratory examination results, including the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, serum ITIH4 levels are inversely correlated with serum TNF-α, interleukin-1beta, interleukin-6 and interleukin-17A in humans with acute ischemic stroke. 28 C-reactive protein (CRP) is an acute-phase reaction protein, and its levels can reflect the extent of the systemic inflammatory 34 Our study showed that serum C-reactive protein levels were independently inversely correlated with serum ITIH4 levels in the cohort of patients with ICH. These data suggest that ITIH4 may be an anti-inflammatory factor with protective functions in acute brain injury.…”
mentioning
confidence: 68%
“…In addition, serum ITIH4 levels are inversely correlated with serum TNF-α, interleukin-1beta, interleukin-6 and interleukin-17A in humans with acute ischemic stroke. 28 C-reactive protein (CRP) is an acute-phase reaction protein, and its levels can reflect the extent of the systemic inflammatory 34 Our study showed that serum C-reactive protein levels were independently inversely correlated with serum ITIH4 levels in the cohort of patients with ICH. These data suggest that ITIH4 may be an anti-inflammatory factor with protective functions in acute brain injury.…”
mentioning
confidence: 68%
“…That is, C-reactive protein was significant by the generalized ridge estimator and was not by the ridge estimator. A study conducted in a large population in China reported that a high C-reactive protein level was an independent risk factor for severe intracerebral hemorrhage [38]. The selection of C-reactive protein as a variable associated with increased hematoma volume may reflect the tendency of patients with severe intracerebral hemorrhage to have easier hematoma expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the inflammatory response remarkably affects ICH. Upon the occurrence of ICH, the organism is capable of inducing a systemic inflammatory response while elevating the RDW, WBC, and CRP levels in ICH patients ( 40 , 56 , 57 ). Furthermore, previous reports demonstrated that high RDW reported increased inflammation indices, such as CRP and IL-6 ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%